2012
DOI: 10.1002/smi.2445
|View full text |Cite
|
Sign up to set email alerts
|

First Anxiety, Afterwards Depression: Psychological Distress in Cancer Patients at Diagnosis and after Medical Treatment

Abstract: Cancer patients require special consideration before and after treatment. Anxiety is the symptom that characterizes diagnosis, whereas depression is more common after medical treatment. The head and neck cancer patients were the group with the highest complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 29 publications
3
57
0
5
Order By: Relevance
“…Furthermore, RTs only see patients during their course of radiation therapy. A study examining psychological changes pre and post treatment found that cancer patients had increased anxiety before and during treatment, whereas depression increased posttreatment [17].…”
Section: Rts' Comfort Levelsmentioning
confidence: 99%
“…Furthermore, RTs only see patients during their course of radiation therapy. A study examining psychological changes pre and post treatment found that cancer patients had increased anxiety before and during treatment, whereas depression increased posttreatment [17].…”
Section: Rts' Comfort Levelsmentioning
confidence: 99%
“…It was estimated that approximately 35% of patients with cancer experienced significant distress (Zabora et al, 2001). Prospective study showed that anxiety and depression were prevalent at diagnosis of cancer (Gil et al, 2012;Iwatani et al, 2013). Over 1/3 of patients newly diagnosed with esophageal cancer suffered from significant psychological symptoms, particularly anxiety (Bergguist et al, 2007;Dempster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cada sesión aborda un tema específico: introducción al concepto del sentido (1), cáncer y sentido (2), historia del concepto de sentido (3)(4), fuentes del sentido (5-7), y cierre (8) (Cuadro 1).…”
Section: Descripción De La Intervenciónunclassified
“…Los pacientes diagnosticados de cáncer avanzado (Estadios III y IV) presentan un mayor grado de complejidad, en relación al manejo de síntomas físicos y psicológi-cos (1,2,3) . Por ello, requieren de un modelo de intervención ajustado a sus necesidades.…”
Section: Introductionunclassified